Changes in Chemical Profile and Bioactive Potential of Cascara Water Kefir Probiotic Beverage During Fermentation - Putri, Destiana Adinda; Nalurita, Indah; Pereira, Agostinho Ximenes (Universitas Panji Sakti, 2025)
The global demand for functional food products is on the rise, with probiotic beverages, including water kefir and kombucha, emerging as the preferred options among consumers. Water kefir is produced through the fermentation of sugar-based solutions by water kefir grains and contains an extensive variety of probiotic microorganisms. Cascara, also known as coffee skin, has been recognized as a viable raw material for functional beverages that possess high antioxidant content. Nonetheless, a comprehensive understanding of the alterations in chemical compounds within cascara during the fermentation process remains insufficient, especially regarding the development of water kefir probiotic beverages. This study aims to identify changes in chemical profiles that occur during fermentation of cascara-based water kefir. The research was conducted using a completely randomized design (CRD) method with fermentation times of 0, 24, 48, and 72 hours. The results showed significant increases in total acidity, with lactic acid rising from 2.25% to 8.10% and acetic acid from 1.50% to 5.40%, which correlated with a decrease in pH. Total phenolic content increased from 366.70 mg/L to 514.91 mg/L, while flavonoid content decreased from 703.12 mg/L to 265.62 mg/L. Additionally, tannin and caffeine contents increased significantly during fermentation, on the other hand the sugar content decreased over time. These findings suggest that fermentation enhances the bioactive potential of cascara-based water kefir, improving its antioxidant capacity while altering its flavor and chemical composition. This research contributes to the understanding of cascara's potential for probiotic beverages, providing valuable insights for the development of functional beverages. The suggestion for further research is the need to identify the bioactive effect of cascara water kefir beverages products on health benefit.